Analis Sosiologis Pernikahan Islam: Antara Norma Agama Dan Perubahan Sosial - Mudassir; Rusly, Fathullah; Yuliardy Nugroho, Irzak (Maqasid: Jurnal Studi Hukum Islam, 2025)
Abstract: Marriage in Islam has a strong theological foundation, governed by religious norms that aim to realize a harmonious family life and be loved by Allah SWT. These norms include the obligation of dowry, the presence of guardians, and the contract process in accordance with Islamic law. However, the social changes affected by modernization, globalization, and digitalization1 have brought new challenges in the implementation of Islamic marriages. Phenomena such as shifting gender roles, increasing cross-cultural marriages, and marriage traditions that increasingly highlight the element of materialism are issues that need to be studied in depth. The study shows that although social changes have a significant influence on the practice of marriage, religious values remain the main foundation for Muslims in exercising marriage. This article also emphasizes the importance of an adaptive approach to bridging the gap between religious norms and social change, so that Islamic values remain relevant in the context of a dynamic society. Keywords: Islamic Marriage, Religious Norms, Social Change, Muslim Family, Cultural Transformation.